Nonsingular Terminal Sliding-Mode Control of Second-Order Systems Subject to Hybrid Disturbances - He, Xinyi; Li, Xiaodi; Song, Shiji (IEEE transactions on circuits and systems. II, Express briefs, 2022)
This brief proposes a novel terminal sliding-mode (TSM) control design for second-order systems subject to both continuous and impulsive disturbances. The problem of singularity is effectively eliminated via the proposed approach. To ensure existence of the sliding mode in the presence of hybrid disturbances, necessary constraints on disturbances are given. It shows that the system can reach the sliding surface within finite time, and then converge to the origin within finite time under the proposed TSM control, which achieves finite-time stabilization of second-order systems. Finally, numerical examples are given to validate the obtained results.